2019
DOI: 10.1039/c9ra01396b
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive Raman detection of human recombinant interleukin-6 mediated by DCDR/GERS hybrid platforms

Abstract: An analytical hybrid platform combining DCDR and GERS effects is presented. An absolute mass detection of 1 fg of IL-6 was reached.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…O-Cuevas et al (23) describe the Raman spectrum of IL-6 showing bands at 938, 1261 and 1655 cm-1 due to the C-C stretching of the backbone structure, amide III and amide I, respectively, corresponding to the typical a-helix secondary structure conformation of IL-6. In addition, conventional residues of amino acids, such as the band at 708 cm-1, indicates the C-S stretching of cysteine residues in the IL-6 structure.…”
Section: Discussionmentioning
confidence: 99%
“…O-Cuevas et al (23) describe the Raman spectrum of IL-6 showing bands at 938, 1261 and 1655 cm-1 due to the C-C stretching of the backbone structure, amide III and amide I, respectively, corresponding to the typical a-helix secondary structure conformation of IL-6. In addition, conventional residues of amino acids, such as the band at 708 cm-1, indicates the C-S stretching of cysteine residues in the IL-6 structure.…”
Section: Discussionmentioning
confidence: 99%
“…This band region includes the C-C ring stretching vibrations of a number of amino acids, which in skin would be primarily proline, hydroxyproline ( Erckens et al, 1997 ; Talari et al, 2015 ; Hernández et al, 2016 ), tyrosine, and tryptophan ( Talari et al, 2015 ; Hernández et al, 2016 ). The latter two compounds are among the cytokines which are increased in inflammatory skin conditions ( Portugal-Cohen et al, 2012 ; de la O-Cuevas et al, 2019 ). Although none of the effects of time-point on the loading areas in this region were significant, the value of p s close to 0.1 between baseline and post-intervention, and between post-stressor and post-intervention support the preference for this region of post-intervention scores.…”
Section: Discussionmentioning
confidence: 99%
“…In this direction, a proof of concept was shown wherein the combination of drop-coating deposition, Raman spectroscopy and graphene-enhanced Raman spectroscopy was used for IL-6 detection. The study was able to detect IL-6 even in 1 μL sample having IL-6 concentration of 1 pg/mL ( de la O-Cuevas et al, 2019 ), however, the sensitivity of the sensor was found to be affected with the substrates used. In case of silicon (Si) substrate, the detection limit was found below 1 ng/mL, but with reduced graphene oxide/silicon substrate (rGO/Si), the detection limit was found even below 1.0 pg/mL, i.e.…”
Section: Inflammatory Biomarkers and Their Detection Platformsmentioning
confidence: 99%